Synthesis Characterization and Optical Properties of Nanostructured Zinc Sulfide Thin Films Obtained by Spray Pyrolysis Deposition - Faris, Rawaa A.; Dhahir, Mohamed K. (Iraqi Journal of Laser, 2019)
In this work, nanostructure zinc sulfide (ZnS) thin films at temperature of substrate 450 oC and thickness (120) nm have been produced by chemical spray pyrolysis method. The X-Ray Diffraction (XRD) measurements of the film showed that they have a polycrystalline structure and possessed a hexagonal phase with strong crystalline orientation of (103). The grain size was measured using scanning electron microscope (SEM) which was approximately equal to 80 nm. The linear optical measurements showed that ZnS nanostructure has direct energy gap. Nonlinear optical properties experiments were performed using Q-switched 532 nm Nd:YAG laser Z-scan system. The nonlinear refractive index (n2) and nonlinear absorption coefficient (β) estimated for ZnS nanostructure for different intensities of laser beam. It has been found that n2 and β were decreased with increasing of intensity of incident laser beam. Also, two photon absorption has been observed. The first type of n2 was positive nonlinear reflective index and the second type of n2 was self-focusing nonlinear refractive index for the sample.